PROJECT BASED LEARNING METHODS USED AT PAI-BP SUBJECT MATERIAL FAITH IN THE HOLY BOOKS OF ALLAH IN COVID-19 PANDEMIC ERA - Misbakhul Munir (Kementerian Agama Prov Jawa Tengah, 2022)
Covid-19 virus can change many things; one of them is educational division. In education, teachers and students are forced to use technology of telecommunications to minimize spreading Covid-19 virus. The teachers and the students need adaptation on on-line learning system. During the adaptation some problem appears, so force the teacher to think to innovate their teaching. Using Project Based Learning method is one of alternative to solve the online learning problems, where the students are often inactive when online teaching and learning takes a place. It makes the students’ result of study decreases, where it happened to 8th grade of Junior High school SIC. By using Project Based Learning method is baled to increase the students’ result of the study, activeness, and creativity.